1994
DOI: 10.1002/mc.2940090404
|View full text |Cite
|
Sign up to set email alerts
|

Influence of DNA repair by ada and ogt alkytransferases on the mutational specificity of alkylating agents

Abstract: We investigated the influence of the alkyltransferases (ATases) encoded by the ada and ogt genes of Escherichia coli on the mutational specificity of alkylating agents. A new mutational assay for selection of supF- mutations in shuttle-vector plasmids was used. Treating plasmid-bearing bacteria with N-methyl-N-nitrosourea (MNU), N-ethyl-N-nitrosourea (ENU), and ethyl methanesulfonate (EMS) dramatically increased the mutation frequency (from 33-fold to 789-fold). The vast majority of mutations (89-100%) were G:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…At both loci, the incidence and the location of GC4AT transitions are consistent with the hypothesis that O6-alkylguanine is the main determinant of CCNU mutagenicity. Alkylnitrosoureas preferentially cause GC4AT transitions at Gs preceded by a Pu residue in E. coli (Jurado et al, 1995;RoldaÁ n-Arjona et al, 1994;Richardson et al, 1987;Burns et al, 1988) and in eukaryotes (Inga et al, 1995;Kunz and Mis, 1989;Minnick et al, 1992;Moriwaki et al, 1991;Palombo et al, 1992). The 5'-¯anking purine eect has been explained as the consequence of a structural in¯uence on the initial formation of O6-alkylguanine, which may be further enhanced by alkylation speci®c repair (Horsfall et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…At both loci, the incidence and the location of GC4AT transitions are consistent with the hypothesis that O6-alkylguanine is the main determinant of CCNU mutagenicity. Alkylnitrosoureas preferentially cause GC4AT transitions at Gs preceded by a Pu residue in E. coli (Jurado et al, 1995;RoldaÁ n-Arjona et al, 1994;Richardson et al, 1987;Burns et al, 1988) and in eukaryotes (Inga et al, 1995;Kunz and Mis, 1989;Minnick et al, 1992;Moriwaki et al, 1991;Palombo et al, 1992). The 5'-¯anking purine eect has been explained as the consequence of a structural in¯uence on the initial formation of O6-alkylguanine, which may be further enhanced by alkylation speci®c repair (Horsfall et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Our results have demonstrated that it is a very effective way of evolving enzyme/protein in vitro. In comparison to whole plasmid mutagenesis (Roldan-Arjona et al, 1994), our approach has the advantage of eliminating the potential phenotype changes caused by mutations outside the target region, such as mutations resulting in change of plasmid copy numbers and regulatory signals for transcription and translation. An obvious extension of this approach would be to further narrow the target region.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, all strains we examined had similar incidences of GC→AT transitions ( Table 2) that occurred in similar sequence contexts (more than 96% were preceded 5´ by a purine) ( Table 4). It is known that alkylnitrosoureas preferentially cause GC→AT transitions at Gs preceded by a purine residue in E. coli [9,32,33] and in eukaryotes [1,34,35]. The 5´-flanking purine effect has been explained as the consequence of structural influence on the initial formation of O 6 -chloroethylguanine that may be further enhanced by sequence-specific repair [36].…”
Section: Discussionmentioning
confidence: 99%